Multidisciplinary Tinnitus Research: Challenges and Future Directions From the Perspective of Early Stage Researchers - Simoes, Jorge Piano; Daoud, Elza; Shabbir, Maryam; Amanat, Sana; Assouly, Kelly; Biswas, Roshni; Casolani, Chiara; Dode, Albi; Enzler, Falco; Jacquemin, Laure; Joergensen, Mie; Kok, Tori; et al. (Frontiers in Aging Neuroscience, 2021)
Tinnitus can be a burdensome condition on both individual and societal levels. Many aspects of this condition remain elusive, including its underlying mechanisms, ultimately hindering the development of a cure. Interdisciplinary approaches are required to overcome long-established research challenges. This review summarizes current knowledge in various tinnitus-relevant research fields including tinnitus generating mechanisms, heterogeneity, epidemiology, assessment, and treatment development, in an effort to highlight the main challenges and provide suggestions for future research to overcome them. Four common themes across different areas were identified as future research direction: 1. Further establishment of multicenter and multidisciplinary collaborations; 2. Systematic reviews and syntheses of existing knowledge; 3. Standardization of research methods including tinnitus assessment, data acquisition, and data analysis protocols; 4. The design of studies with large sample sizes and the creation of large tinnitus-specific databases that would allow in-depth exploration of tinnitus heterogeneity.